2016
DOI: 10.2147/ijnrd.s89128
|View full text |Cite
|
Sign up to set email alerts
|

Health status, renal function, and quality of life after multiorgan failure and acute kidney injury requiring renal replacement therapy

Abstract: Background: Critically ill patients with acute kidney injury (AKI) in need of renal replacement therapy (RRT) may have a protracted and often incomplete rehabilitation. Their long-term outcome has rarely been investigated. Study design: Survivors of the HANnover Dialysis OUTcome (HANDOUT) study were evaluated after 5 years for survival, health status, renal function, and quality of life (QoL). The HANDOUT study had examinded mortality and renal recovery of patients with AKI receiving either standard extendend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In the HANDOUT study published in 2016, the authors investigated the QOL post-RRT in general ICU patients. [ 16 ] They reported that their assessment of QOL using the SF-36 did not reveal significant physical limitations in their patient group. This could either be due to the fact that they were able to investigate only a small number of patients (21 patients) as compared to 499 patients in this study and/or they did not have another group for comparison of the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…In the HANDOUT study published in 2016, the authors investigated the QOL post-RRT in general ICU patients. [ 16 ] They reported that their assessment of QOL using the SF-36 did not reveal significant physical limitations in their patient group. This could either be due to the fact that they were able to investigate only a small number of patients (21 patients) as compared to 499 patients in this study and/or they did not have another group for comparison of the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have focused on critically ill patients receiving renal replacement therapy. Results have been varied, with some studies demonstrating a reduction in HRQOL [7,11] while others do not demonstrate a difference in HRQOL following AKI [10,[22][23][24]. Nisula et al did evaluate critically ill adults with varying AKI stages, not just those requiring RRT, and did not find differences in quality of life scores among that cohort [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since QoL data were not collected during the TANGO II study [ 15 ], health utilities were retrieved from literature [ 23 27 ]. The health utilities considered in the analysis were associated to the following health states: (i) hospitalisation without nephrotoxicity [ 27 ], (ii) hospitalisation with nephrotoxicity [ 25 ], (iii) acute RRT [ 25 ], (iv) chronic RRT [ 26 ], (v) discharged home [ 23 ] and (vi) discharged to long-term care (LTC) [ 28 ]. The same utility values were considered in a previously published economic evaluation of CRE population [ 24 ].…”
Section: Methodsmentioning
confidence: 99%